Single-cell transcriptomics reveals cellular heterogeneity and cell–cell communication networks in free gossypol-induced enteritis in juvenile largemouth bass (Micropterus salmoides) - Xinpeng Wang; Wanying Jiang; Linlin Li; Jun Wen; Limeng Wang; Shimei Lin; Yongjun Chen; Li Luo; Xinghua Zhou; Yuanfa He (Fish & Shellfish Immunology, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Contrasting impacts of biodegradable and conventional microplastics on heavy metal bioavailability in soils: A multilevel meta-analysis - Xue-Dan Cui; Zheng-Xiao Jiang; Yi-Hao Mei; Ting-Ting He; Xiao Tan; Ai-Jun Lin; Gui-Lan Duan (Environmental Pollution, 2026)

Crystallinity-dependent PMS activation by ZnFe2O4 spinel enables radical-dominated degradation of imidacloprid under microwave irradiation - Yang Zhou; Xitao Liu; Jun Huang; Yanwei Zhao; Chunye Lin; Mengchang He; Wei Ouyang; Shouliang Huo (Chemical Engineering Journal, 2026)

W-PDA/Au nanohybrid-based ternary immunosensor for simultaneous detection of PCT, IL-6, and CRP toward efficient sepsis diagnosis - Lin Jin; Yi Shen; Wei Jin; Xu Tao; Jinwu Hu; Shujuan Mao; Jin tao Li; Hui-jun Li; Ding Wang; Yuan Zhang; Bin He (Chemical Engineering Journal, 2026)

Engineered bacteria as ultrasound-responsive carbon monoxide vehicles for Cancer gas therapy and synergistic immunotherapy - Xiaorui Chen; Xiao Xiao; Wei Zhao; Bin Liu; Hongzhou Lian; He Ding; Piaoping Yang; Ping'an Ma; Lingjie Song; Shifang Luan; Ziyong Cheng; Jun Lin (Chemical Engineering Journal, 2026)

Extracellular polysaccharide-facilitated selenium nanoparticle assembly and metabolic reprogramming support efficient selenite biotransformation by ARTP-mutagenized Lactiplantibacillus plantarum Vse252 - Lihui Tan; Xinyan Wang; Lin Hu; Xiang Gen; Shirui Yu; Xue Li; Xinyu Yan; Bo He; Jun Zhang; Yongzhong Wang; Hengqian Lu (Bioresource Technology, 2026)

Repeated long-term cover cropping and nitrogen fertilization enhance soil multifunctionality - Lin Li; Wanyu He; Qilong Du; Xue Zhao; Minghui Meng; Guangjin Wu; Guangxi Liu; Simeng Wang; Jun Wang; Fazhu Zhao; Jieying Wang (Agriculture, Ecosystems & Environment, 2026)

Albafurans D−N, 2-phenylbenzofuran derivatives with anti-inflammatory activity from Morus alba - Jun-Sheng Zhang; Lin-Lin Tian; Quan-Hao Wei; Meng-Jie He; Hua Zhang (Phytochemistry, 2026)

Precise radical quantification and process optimization of UV/persulfate advanced oxidation for sertraline removal - Xiaofeng Zeng; Wenbo Ren; Xitao Liu; Yanwei Zhao; Jun Huang; Chunye Lin; Mengchang He; Wei Ouyang; Shouliang Huo (Journal of Environmental Chemical Engineering, 2026)

Urban sidewalk detection via a cross-view joint segmentation method using satellite and street-view imagery - Yi Lin; Weijia Li; Jinhua Yu; Junyan Ye; Jun He; Xiang Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

One-pot dual-crosslinked gelatin/alginate hydrogels for microstructure and texture regulation in 3D-printed meat analogues - Chunling Que; Jieqiong Lin; Yuan Xu; Xianxiang Chen; Yanfu He; Evi Paximada; Chuan Li; Jun Yang (Food Chemistry, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Dual enhancement of carbon-based catalysts via Maillard reaction: Boosting peroxymonosulfate activation and facilitating 1O2 production - Xiaoyu Ma; Xitao Liu; Jun Huang; Yanwei Zhao; Chunye Lin; Mengchang He; Wei Ouyang; Shouliang Huo (Chemical Engineering Journal, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

Microplastic type influences soil phosphorus availability independently of long-term cropping systems and fertilization regimes - Xuechen Yang; Lin Han; Raúl Ochoa-Hueso; Jingjie Dou; Peng He; Yakov Kuzyakov; Wenzheng Song; Xiaowei Wei; Yueyu Sui; Xiangxiang Hao; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2026)

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Transformation characteristics of typical antidepressants in UV-advanced oxidation processes - Wenbo Ren; Xitao Liu; Yanwei Zhao; Jun Huang; Chunye Lin; Mengchang He; Wei Ouyang; Shouliang Huo (Journal of Hazardous Materials, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

A photothermal catalytic system based on phase change energy storage COF gel composites for solar-driven water-H2O2-electricity co-production - Shuping Jia; Weixiong Dong; Hongrui Jiang; Hongmei Li; Zhiqing Lin; Jun He (Chemical Engineering Journal, 2026)

Effects of norgestrel on the reproductive endocrine system, hepatic damage and antioxidant responses of marine medaka (Oryzias melastigma) at different salinities - Jian Song; Chao Zheng; Yan-Qiu Liang; Zhongdian Dong; Chang-Gui Pan; Wen-Jun Shi; Qidan Zheng; Shuhui Zhou; Mingwei He; Xipeng Mo; Zhong Lin (Aquatic Toxicology, 2026)

The mixed cover crops and nitrogen fertilization decrease the soil microbial dormancy - Simeng Wang; Xue Zhao; Wanyu He; Jieying Wang; Minghui Meng; Xiya Xiong; Min Xie; Guangjin Wu; Qilong Du; Lin Li; Guangxi Liu; Jun Wang; et al. (Plant and Soil, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Contact detection and contact indeterminacy identification for general polyhedrons based on contact theory - Shaozhong Lin; Jun He; Dongdong Xu (Computers and Geotechnics, 2026)

Ultrastructural response of the retinal cells and neurovascular unit to neuroinflammation induced by lipopolysaccharide - Bilin Rao; Xiaotian Wu; Xiaoqing Liu; Fenglan Wang; Fang He; Xin Lin; Guiyu Guan; Xiaoqian Lai; Jun Zhang (Brain Structure and Function, 2026)

Deciphering the spatial patterns of a springtime microbial community: Structure, function, and key drivers in the Southern Yellow Sea - Yang Yuan; Wei He; Long Jiang; Lin-Qiong Wang; Xian-Pu Ji; Dao-Feng Zhang; Wen-Jun Li (Journal of Environmental Sciences, 2026)

Lanthanum-modified biochar for dual removal of particulate/dissolved phosphorus in agricultural runoff: Performance and reuse as slow-release fertilizer - Ting Chen; Jiayi Lu; Fenghao Lin; Zhiqiang Chen; Junjie Wei; Jie He; Ying Wang; Xiujuan Tang; Jun Yin (Journal of Environmental Sciences, 2026)

Compositional profiling and inter-cultivar variation of flavonoids in some red table grapes cultivated in China: Assessing the quality-indicative potential of anthocyanins, flavonols, and flavanols - Shang-Lin Wang; Hai-Bei Yan; Lin Wang; Xing-Chi Chen; Jun Wang; Fei He (Food Chemistry, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Targeting perivascular adipose tissue in vascular aging: innovative translational strategies for disease prevention and monitoring - Peng-Xin Wang; Sha-Qi He; Bei Huang; Zi-Fei Liu; Feng Xu; Jun-Jie Yang; Sai Lu; Hui-Xiang Chen; Ze-Qiang Cai; Ling-Qing Yuan; Xiao Lin (Apoptosis, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Characterization of streptomycin-induced persister cells in Erwinia pyrifoliae - Lin He; Jun Myoung Yu (Physiological and Molecular Plant Pathology, 2026)

Germinated quinoa flour as a functional ingredient in wheat bread: Impact on dough microstructure, rheology, and nutritional-sensory profile - Yanan He; Yaxuan He; Jiayin Huang; Huan Sun; Lin Cheng; Jing Zhang; Jun Liu; Haijie Liu (Food Hydrocolloids, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

An Enzymatic Recombinase Amplification Coupled Lateral Flow Assay for Rapid, Visual, and Cost-Effective Detection of Bordetella pertussis - Piaoting Wen; Jian Liu; Mingqi Jiao; Hangxi Liu; Mei Lin; Sheping Zhang; Jun He; Ziyi Li; Changhui Xiao; Zhongliang Deng (Current Microbiology, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

The effects of Polygonum capitatum in treating atopic dermatitis via modulation of the th2 cytokine pathway - Xiao-Gang Sun; Bin-He Yang; Xiao-Lin Yang; Fei Li; Li-Jun Hao (South African Journal of Botany, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Enrichment of organophosphate esters in the surface microlayer of a subtropical urban lake: Phase partitioning dynamics and air-water exchange implications - Mingfu Lin; Tao He; Rong Wang; Lixiang Zhong; Menghuan Zhang; Jun Wang; Yumei Huang (Journal of Hazardous Materials, 2026)

Synergistic control of LixV2O5 with ordered-disordered hybrid rock-salt structure via chemical lithiation: Enhanced Li-ion battery performance - Wei He; Bei-Lei Yan; Wei-Wei Meng; Guang-Qiang Ma; Xue-Jun Zhu; Xue Hua-Mao; Lin Deng; Hong-Wei Ge; Tao Yang; Jun Wang (Chemical Engineering Journal, 2026)

Enhancing Fenton-like degradation with Co1-xS@C under neutral and alkaline environment: Unveiling the role of reactive microenvironment - Xiaoyu Ma; Xitao Liu; Jun Huang; Yanwei Zhao; Chunye Lin; Mengchang He; Wei Ouyang (Chemical Engineering Journal, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Targeting the gut-liver axis with dietary polyphenols to ameliorate metabolic dysfunction-associated steatotic liver disease: advances in molecular mechanisms - Zuomin Hu; Zeyu He; Yuyan Wang; Zhongxing Chu; Yaping Zhou; Wen Li; Jun Lu; Qinlu Lin; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2026)

Multi-omics analysis investigates the effects of replacing fishmeal with intestinal mucosal protein on growth performance and intestinal health in hybrid sturgeon - Yuanfa He; Jun Wen; Hang Chen; Guangjun Lv; Yongjun Chen; Shimei Lin; Haiping Liu; Zhijian Wang; Hailong Ge (Aquaculture, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Magnetic properties driving nitrogen removal improvement in magnetite-enhanced activated sludge: Mechanistic insights and process validation - Jun Shi; Luo-Kai Li; Li-Han Lin; Duo-Kun Li; Jian Lu; Sali Mustafa Saleh; Tian-Yang Zhang; Huan He; Zheng-Yu Dong; Qian Xiao; Bin Xu; Chao Zeng (Environmental Research, 2026)

Boron and oxygen isotopes fractionation between borate minerals and fluids and implications for borate deposit formation - Da-Sheng Zuo; Hai-Zhen Wei; Jian-Jun Lu; M.R. Palmer; A.E. Williams-Jones; Jun-Lin Wang; Shao-Yong Jiang; Ke Yang; He-Feng Lin; Simon V. Hohl; Yi-Chu Chen (Applied Geochemistry, 2026)

Plant‐Induced Transcriptional Plasticity Diverges Between Generalist and Specialist Herbivores - Jun Wu; Zhimou Lin; Guomeng Li; Wenyuan Yu; Yangzhi Zhang; Yishuo Kou; Pengshuai Peng; Tingfen He; Yu Wang; Shuai Zhan; Jean‐Christophe Simon; Saskia A. Hogenhout; et al. (Molecular Ecology, 2026)
Most herbivores are specialised on particular host plants but some are generalists that can exploit distinct hosts. Generalists may have evolved adaptive transcriptional plasticity to cope with the defences of the different hosts. However, the fundamental differences in plant‐induced transcriptional plasticity between generalists and specialists remain poorly understood. Here, we investigated transcriptional plasticity of the generalist aphid Myzus persicae and two specialist aphids, Brevicoryne brassicae and Rhopalosiphum padi , by transferring them between Brassica napus (a host for B. brassicae but not for R. padi ) and Zea mays (a host for R. padi but not for B. brassicae ), both suitable hosts for M. persicae . Generalist and specialist aphids exhibited transcriptional plasticity coordinately in response to different plant species, but their gene expression patterns often diverged. Generalist aphids attenuate the activation or even suppress salicylic acid (SA) signalling in host plants, whereas specialist aphids provoke it in nonhost plants. SA signalling had limited effects on gene expression in the generalist aphids, but significantly shaped transcriptional responses of the specialists. These findings underscore the fundamental differences in plant‐induced transcriptional plasticity between generalists and specialists and highlight the critical role of plasticity directionality in insect adaptation.

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Research on rule of law system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area - Ke Zhang; Er-He Chen; Yu-Lin Chen; Jun-Jie Li; Tao Huang; Wei Liu; Si-Hao Wei; Yu-Kang Tu (Frontiers in Marine Science, 2026)
The development of a legal system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area is a critical issue for cross-border ecological governance under the unique context of "One Country, Two Systems, Three Jurisdictions." This issue directly affects regional ecological security and the high-quality development of the marine economy. This paper uses comparative law and empirical analysis to systematically review the institutional frameworks and current practices of the three regions across four dimensions: Legislation, law enforcement, judicial adjudication, and legal regulation of public participation. The study finds that the current system faces core difficulties, including a disconnect in legislative coordination mechanisms, insufficient effectiveness in joint law enforcement, uncoordinated judicial collaboration, and insufficient legal safeguards for public participation. The root causes lie in the differences between regional legal systems, the absence of coordination mechanisms, poor resource integration, and fragmented participation channels. Based on this, the paper proposes a comprehensive improvement path. At the legislative level, we should establish a normalized coordination mechanism to promote the alignment of rules and standards. At the enforcement level, we should build a unified coordination platform to deepen cross-border collaboration and resource sharing. At the judicial level, we should improve cross-border collaboration norms and improve mechanisms for identifying and repairing ecological damage. At the level of public participation, we should build a unified cross-border platform to strengthen collaborative systems and public interest cooperation. The research aims to provide a governance model for regional marine environmental protection under "One Country, Two Systems, Three Jurisdictions," offering theoretical support and practical guidance for solving cross-border ecological governance problems, and assisting in the construction of a strong maritime nation and the improvement of the global marine governance system.

A new method to determine the surrounding rock pressure in twin tunnels with small clear spacing - Zhiyu Tian; Chuan He; Guowen Xu; Guojin Lin; YueHeng Shu; Jun Wang; Liang Nie (Tunnelling and Underground Space Technology, 2026)

Microplastics enhance soil nitrogen availability by stimulating nitrogen-acquiring enzyme activity over three decades-long fertilization regimes - Lin Han; Jingjie Dou; Kai Zhu; Lu-Jun Li; Peng He; Xiaowei Wei; Xiaojing Hu; Yueyu Sui; Xiangxiang Hao; Xuechen Yang (Soil and Tillage Research, 2026)

RSK2 facilitates beige fat formation through thermogenic and glycolytic pathways - Yan Cai; Jun-jun Chen; Lin-fei He; Yao Xu; Rui-qi Yang; Zhi-chun Yang (Journal of Thermal Biology, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

SEMA3E promotes beige adipocyte differentiation and thermogenesis via β-catenin signaling in mice - Chenxi Xiao; Zhenghua Su; Jialin Zhao; Yajie Hu; Mengting He; Shenhan Xu; Ruoxue Chen; Jie Xu; Jun Chang; Chengshou Lin; Xinhua Liu; Wugui Chen (Apoptosis, 2026)

Comparative pharmacokinetics of sixteen components following oral administration of raw and processed Viticis Fructus in rats - Zijing Zhang; Kaili Zhang; Wenwen Li; Zhenguo Lv; Lu Chen; Jinyue Ma; Wenhan Lin; Yameng Zhu; Huizi Ouyang; Jun He (Natural Product Research, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Optimization design of linear seal structures in marine electric pumps - Zongbin Chen; Jun Che; Lin He; Jian Liao; Yantao Zhang (Ocean Engineering, 2026)

Nonlinear microbial nutrient limitation responses to biodegradable vs. conventional microplastics under long-term agricultural management - Jingjie Dou; Lin Han; Xiaojing Hu; Lu-Jun Li; Peng He; Junhui Wang; Xiangxiang Hao; Yueyu Sui; Wei Sun; Xuechen Yang (Journal of Hazardous Materials, 2026)

Spatiotemporal pattern of vegetation evolution in northeastern Tibetan Plateau during the Cenozoic and its climatic significance - Yun-Xia Jia; Wen-Chao Zhang; Li-Jun Tian; Zhi-Lin He; Zhao Wang; Qing-Chun Tian (Palaeoworld, 2025)

Cradle-to-gate carbon footprint of industrial-scale fermentative production of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) - Hsien-Tse Chen; Yu-Hsiang He; Pei-Yi Lin; Wei-Shu Huang; Kaarmukhilnilavan R. Srinivasan; Jun-You You; Pei-Yu Sun; Allen H. Hu; Penjit Srinophakun; Maythee Saisriyoot; Si-Yu Li (Journal of Cleaner Production, 2025)

Seismic performance of a low yield point steel link with corrugated web for RC double-column bridge bent - Sidong Feng; Jun He; Wei Fan; Weiwei Lin; George Vasdravellis (Engineering Structures, 2025)

Non-decomposition method for event-triggered finite-time synchronization control of complex-valued memristive neural networks - Hui Lin; Yanchao Shi; Jun Guo; Xiaoya He (Cognitive Neurodynamics, 2025)

Distinct cellular localization of α- synuclein and β-synuclein in the chick retina - Fang He; Lin Liu; Shaoxuan Wang; Xin Lin; Guiyu Guan; Xiaoqian Lai; Xi Yu; Xiaotian Wu; Zhihao Shen; Bilin Rao; Mei-Ling Gao; Xuejiao Chen; et al. (Brain Structure and Function, 2025)

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

A novel high selectivity, strong acid resistance and antifouling polyamide thin film composite nanofiltration membrane fabricated with 3,3′-diamine-Tröger's base - Liu-Yang Gong; Nian Zhang; Jun-Yan Yu; Yan-Nan Wu; Chen-Jie Wei; He-Lin Zhu; Xue-Li Cao; Li-Fen Liu (Desalination, 2025)

Candidate pathway for low-carbon methanol production from coke oven gas and biogas: A multi-dimensional techno-economic and environmental analysis - He Zhu; Yutong Lin; Jing Tian; Zhichao Li; Yidan Zhang; Shuqing Li; Yuhan Sun; Jun Zhang (Chemical Engineering Journal, 2025)

A bifunctional fluorescent probe for simultaneous imaging of myelin integrity and β-amyloid plaques in Alzheimer's disease progression - Xueting Wang; Huan Liu; Xueao Wang; He Wang; Jie Lin; Xiangjie Luo; Jian-Jun Yang; Bing Zhang; Guiquan Chen; Hai-Liang Zhu; Tony D. James; Yong Qian (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Subtropical EM- surpass AM-dominated forests in increasing soil inorganic nitrogen availability: Evidence from a controlled field experiment - Yiting Qiu; Hang-Wei Hu; Hao Yang; Xiaoyu Chen; Jiamian Shi; Guigang Lin; Liuming Yang; Shengsheng Jin; Guangshui Chen; Jun-Tao Wang; Zhiqun Huang; Ji-Zheng He; et al. (Pedobiologia, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Sustained moderate oxidation system driven by gas-liquid-solid microenvironment under Mn(VII)-Fe(III)/sodium percarbonate (SPC) treatment: Mechanism and application in sludge dewatering - Wei Lin; Chuangxin Gong; Xiuxiang Ding; Xu He; Jun Ma; Mohamed E.A. Ali; Ahmed Shahat; Piotr Oleskowicz-Popiel; An Ding (Journal of Environmental Chemical Engineering, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Hydrogels with anti-inflammatory modulation microniches for tendon repair - Tao Zhou; Tao Ma; Qiankun Wang; Zifu Wang; Jun Huang; Lin Zhong; Ding Zhou; Zhe Jin; Yang Niu; Dong Yin; Tianyou Hu; Yujie Bian; et al. (Chemical Engineering Journal, 2025)

Enhancing high-temperature phase stability and thermal properties of 5RE(TaxNb1-x)O4 high-entropy ceramics through chemical bonding strength optimization - Mengdi Gan; Liping Lai; Xiaoyu Chong; Qianqian Jin; Wei Yu; Jiankun Wang; Jun Wang; Lin Chen; Jingjin He; Jing Feng (Chemical Engineering Journal, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Preparation of UCO sols suitable for gelation into microspheres by sol–gel process with glucose - Wenjing Zhang; Chao Yan; Xiaohe Yu; Changqing Cao; Jun Lin; Guobao Zhang; Bolong Guo; Fan Zhang; Xiuyan Dong; He Huang (Annals of Nuclear Energy, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Seismic scattered wave direct imaging in shallow underground space with undulating surface - Ke Shi; Feng Xu; Zong-ling Yan; He-jun Chai; Xue-ming Jia; Xing-lin Lu; Xian-xin Liu; You-ping Mao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Low temperature hydrochar from sewage sludge enhancing polyacrylamide-based preformed particle gels with high temperature and salinity tolerance - Bei-Bei Wu; Yan-Yan Xu; Fan Gao; Ya-Jun Wu; Lin-Hui Xi; Zhi Kang; Hong-Kui He; Zu-Guo Yang; Zhi-Xiang Xu (Journal of Water Process Engineering, 2025)

Mechanochemical degradation of UV-328 by solid oxidative reagents: Peroxydisulfate vs. peroxymonosulfate - Xiwang Zhao; Xitao Liu; Jun Huang; Chunye Lin; Mengchang He; Wei Ouyang (Journal of Hazardous Materials, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Bclaf1 mediates super-enhancer-driven activation of POLR2A to enhance chromatin accessibility in nitrosamine-induced esophageal carcinogenesis - Xiangjun Zhou; Xueqiong Zhou; Jun Li; Yingzheng He; Shizhen Qiu; Ye Xu; Zeyu Liu; Yina Yao; Jia Liu; Ying Wen; Sitong Xie; Jialong Chen; et al. (Journal of Hazardous Materials, 2025)

Electrocatalytic upcycling of polylactic acid hydrolysate and simultaneous hydrogen production - Ping He; Jiang-nan Xu; Jia-yang Dou; Bing Xu; She-ying Dong; Ting-lin Huang; Jun-Jie Zhu (Chemical Engineering Journal, 2025)

A century of advances in molecular genetics and breeding for sustainable resistance to rice blast disease - Xilai Huang; Wei Yao; Qianru Chen; Jinjun Lin; Jun Huang; Yuying Zou; Chenglong Guo; Bei He; Xiao Yuan; Chengyang Xu; Xionglun Liu; Yinghui Xiao; et al. (Theoretical and Applied Genetics, 2025)

Impact on nonlinear runoff of LID facilities and parameter response in the TVGM model - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiang Wang; Wei Luo; Jianliang He; Jun Xia (Journal of Hydrology, 2025)

Effects of semipermeable membrane-covered composting on greenhouse gas mitigation and microbiome at different ambient temperatures at an industrial scale - Junwei Yuan; Siyuan Lin; Yi Wang; Wenxiang He; Yangyang Li; Junda Wu; Liang Cai; Xiaoyan Kong; Dongqi You; Bo Liu; Jun Hou (Journal of Environmental Chemical Engineering, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Use of non-targeted metabolomics to explore metabolic differences between stem cells and callus of Tetraena mongolica - Yeru Yang; Haihua Li; Ruiping Wang; Jiahe Li; Ling Li; Jiayu Li; Lin Ou; Jun Li; Chengbo Zhang; Liyu Wang; Fengqiang Yu; Zhi He; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Natural promising daphnane diterpenoids: An integrated review of their sources, structural classification, biological activities, and synthesis - Kang Ding; Xuege Pan; Weifeng Yin; Lin Li; Hongjin Bai; Maoli Bai; Jiekun Xu; Jun He; Weiku Zhang (Phytochemistry, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Neural Stem Cell Extracellular Vesicles Carrying YBX1 Inhibited Neuronal Pyroptosis Through Increasing m6A-modified GPR30 Stability and Expression in Ischemic Stroke - Jun Peng; Jun He; Long Lin; You Li; Ying Xia (Translational Stroke Research, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

A continental record of Early Cretaceous (Aptian) vegetation and climate change based on palynology and clay mineralogy from the North China Craton - Chang Lu; Miao-Qin Lin; Jun Shen; Xing-Kai Ji; Chuan-Mao Yang; Zhi-Hua Zhang; Qian He; Ming-Dao Sun; Yi-Gang Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Concurrent optimization of truss structures and build directions for multi-axis additive manufacturing - Jun Ye; Xiaoyang Lin; Hongjia Lu; Linwei He; Guan Quan; Cheng Huang; Paul Shepherd (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

Three-dimensional Finite-Element Forward Modeling and Response Characteristic Analysis of Multifrequency Electromagnetic - Jun Zhou; Ke He; Zhi-yan Liu; Shuai Ruan; Hong-lin Ran (Applied Geophysics, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

Microglia heterogeneity during neuroinflammation and neurodegeneration in the mouse retina - Bilin Rao; Xiaoqing Liu; Jiayi Xiao; Xiaotian Wu; Fang He; Qingwen Yang; Wenna Zhao; Xin Lin; Jun Zhang (Brain Structure and Function, 2024)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Egg production monitoring in commercial laying cages via the StrongSort-EGG tracking-by-detection model - Rui Wu; Pengguang He; Yefan He; Jun Dou; Mengzui Di; Shupeng He; Khawar Hayat; Yi Zhou; Lin Yu; Jinming Pan; Hongjian Lin (Computers and Electronics in Agriculture, 2024)

Estimation of suspected estrogenic transformation products generated during preservative butylparaben chlorination using a simplified effect-based analysis approach - Jie Ouyang; Min Lin; Fang Wei; Chen Ling; Tingyu Lu; Yao Liu; Beimeng Qi; Jun Hu; Jian He; Guoqiang Zhuang (Water Research, 2024)

Pilot-scale study of turbid particle evolutional/removal characteristics during coagulation-sedimentation-filtration (CSF): Effects of coagulant dosage and secondary dosing after breakage - Dan Xiao; Jun Nan; Xiaoyue Zhang; Weipeng He; Yaqian Fan; Xianzeng Lin (Journal of Water Process Engineering, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Deep dehumidification characteristics of a silica gel coated cross-flow heat exchanger with a circulating blowing loop - Lin Liu; Hongyu Huang; Jun Li; Yu Bai; Zhaohong He; Lisheng Deng; Tieyu Gao; Mitsuhiro Kubota; Noriyuki Kobayashi (Energy and Buildings, 2024)

The effect of Desulfovibrio caledoniensis and Pseudomonas aeruginosa on the corrosion behaviour of 70Cu-30Ni alloy - Li-Jun He; Zheng-Hui Qiu; Shao-Xia Ma; Rong-Chang Zeng; Cun-Guo Lin (Biofouling, 2024)

Multiple environmental gradients shape the functional structure of macrobenthic communities across the Pacific Arctic shelf - Kun Liu; Yaqin Huang; Weibo Wang; Jianfeng Mou; Junhui Lin; Shuyi Zhang; Longshan Lin; Jun Sun; Zhongyong Gao; Heshan Lin; Xuebao He (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

A three-stage oxidation method improves sludge dewaterability by achieving sustained oxidation and phased enhanced coagulation: Ingeniously using H2O2 as a “converter” - Wei Lin; An Ding; Chuangxin Gong; Xiuxiang Ding; Peter Desmond; Piotr Oleskowicz-Popiel; Xu He; Jun Ma; Huu Hao Ngo (Chemical Engineering Journal, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Experimental investigation on the horizontal impact response of precast RC bridge piers with grouted sleeve connections considering defects - An He; Dun-Cong Zheng; Jian Cai; Qing-Jun Chen; Xu-Lin Tang; Jia-Bin Ye (Engineering Structures, 2024)

Role of polarized and interfacial built-in electric fields in photocatalysts for enhanced photocatalytic performance - Caiyu Luo; Chunping Yang; Jun Xie; Xiang Li; Yan Lin; Shehua Tong; Shanying He (Chemical Engineering Journal, 2024)

Overlooked role of protocatechuic acid in enhancing the selective elimination of sulfonamide antibiotics in Fe(III)/peroxymonosulfate process under actually neutral pH conditions - Sheng Li; Jing Zou; Jianying Wu; Jinbin Lin; Zhijie Wu; Chenyu Tang; Linfeng He; Xiaobin Liao; Jun Ma (Chemical Engineering Journal, 2024)

Relationship between flavor characteristics and lipid oxidation in air-dried beef at different roasting stages - Jiafei Zhu; Weifang Lin; Yangying Sun; Daodong Pan; Qiang Xia; Changyu Zhou; Jun He (International Journal of Gastronomy and Food Science, 2024)

Pre-deposited biochar enhanced flux stabilization and pollutant removal in gravity-driven membrane system - Caihong Liu; Qingyang Zuo; Jingjun Bo; Haiqing Chang; Lin Li; Qiang He; Dan Song; Jun Ma (Chemical Engineering Journal, 2024)

Ternary stabilization strategies for succinonitrile-based in situ polymerized electrolyte enabling high-performance solid lithium metal batteries - Chenyu Lin; Tianqi Yang; Haiyuan Zhang; Donghuang Wang; Wenkui Zhang; Yao Wang; Yang Xia; Hui Huang; Xinhui Xia; Yongping Gan; Xinping He; Xinyong Tao; et al. (Chemical Engineering Journal, 2024)

Uncertainty of canopy interception modeling in high-altitude Picea crassifolia forests of Semi-arid regions - Junjun Yang; Zhibin He; Pengfei Lin; Jun Du; Dong Shi; Meng Bai (Agricultural and Forest Meteorology, 2024)

Spatio-temporal patterns and population exposure risks of urban heat island in megacity Shanghai, China - Dan Liu; Rui Zhou; Qun Ma; Tianxing He; Xuening Fang; Lishan Xiao; Yina Hu; Jie Li; Lin Shao; Jun Gao (Sustainable Cities and Society, 2024)

Assessment of biochar supported sulfidized iron-based nanoparticles for immobilization of cadmium in sediment: Effectiveness, contribution of iron reducing bacteria, and mechanism insight - Jun Li; Qi He; Weilong Lin; Yiqun Xu; Yang Gao; Mingjuan Zhang; Xiaoju Wen; Wenjing Xue (Journal of Cleaner Production, 2024)

Amphichdiral enhancement on singlet oxygen generation and stable thallium immobilization using iron-driven copper oxide - Zhujun Liu; Xinning Dai; Jun He; Mengyi Lin; Hongbing Luo; Liangqian Fan; Ke Zhang; Dandan Ma; Jun Wang; Wei Chen (Journal of Environmental Management, 2024)

Hydrogen peroxide enhanced Cu(II)/peroxymonosulfate system for naproxen degradation in natural water matrix and simultaneously reduced the formation potential of halogenated by-products - Jianying Wu; Jing Zou; Sheng Li; Chenyu Tang; Zhijie Wu; Linfeng He; Jinbin Lin; Qingsong Li; Jun Ma (Chemical Engineering Journal, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

Modulation of evapotranspiration and stream runoff by weathered bedrock in arid and semi-arid mountains - Pengfei Lin; Peng Zhao; Jian Ma; Junjun Yang; Xi Zhu; Quanyan Tian; Jun Du; Longfei Chen; Zhibin He (Science of The Total Environment, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Interfacial competing interaction eliminates voids in the buried interface for efficient and stable perovskite solar modules on bare NiOX - Sibo Li; Xin Wang; Jun Fang; Dongxu Lin; Nuanshan Huang; Daozeng Wang; Sisi He; Longbin Qiu (Chemical Engineering Journal, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Sustained oxidation of Tea-Fe(III)/H2O2 simultaneously achieves sludge reduction and carbamazepine removal: The crucial role of EPS regulation - Wei Lin; Renglu Chen; Chuangxin Gong; Peter Desmond; Xu He; Jun Nan; Guibai Li; Jun Ma; An Ding; Huu Hao Ngo (Journal of Hazardous Materials, 2024)

Microcystin-RR promote lipid accumulation through CD36 mediated signal pathway and fatty acid uptake in HepG2 cells - Wenjuan Jia; Lin Zhong; Qingmiao Ren; Da Teng; Lei Gong; Haibin Dong; Jun Li; Chunxiao Wang; Yong-Xing He; Jun Yang (Environmental Research, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Sorption of cadmium by layered double hydroxides: Performance, structure-related mechanisms, and sequestration stability assessment - Dong Zhang; Zhishun Zhong; Zilong Liu; Shichong He; Jun Lin; Yiyan Lv; Ting Lü; Ying Pan; Huading Shi; Hongting Zhao (Chemosphere, 2024)

Association between blood arsenic concentration and dyslipidemia: Mediating effect of lipid peroxidation in the elderly - Jia-Hui Huang; Yi Wu; Wei He; Jun-Xian Wang; Lin Fu; Xi Chen (Journal of Trace Elements in Medicine and Biology, 2024)

Polynorepinephrine-regulated filler sulfonation toward interfacial reformation and conductive promotion of nanocomposite proton exchange membrane - Tong Huang; Xin Liu; Ruibin Ma; Yangyang Gao; Xiaomin Xu; Chengrun Yan; Yuchen Guo; Xiaoxu Li; Yanzhou Qin; Lingling Liu; Jiandang Xue; Huadong Huang; et al. (Chemical Engineering Journal, 2024)

Ultrasoft bioadhesive hydrogel as a versatile platform for the delivery of basic fibroblast growth factor to repair traumatic brain injury - Bixin Shen; Junhui Wang; Tao He; Shihao Chen; Xue Wang; Jun Chen; Ruiqing Shi; Jing Wang; Hao Wang; Wenting Huang; Chengkun Cao; Xianxi Tan; et al. (Chemical Engineering Journal, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Evaluation of the dietary L-valine on fish growth and intestinal health after infection with Aeromonas veronii - Quanquan Cao; Ju Zhao; Lingjie He; Tianran Zhang; Lin Feng; Weidan Jiang; Pei Wu; Juan Zhao; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

A particle-scale insight into the face stability of shallow EPB shield tunnels in dry cobble-rich soil - Jun Wang; Guojin Lin; Rui Tang; Yan Zhang; Zhigang Yao; Kun Feng; Ning Tian; Ziquan Chen; Chuan He (Tunnelling and Underground Space Technology, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Electrically-assisted anaerobic digestion under ammonia stress: Facilitating propionate oxidation and activating methanogenesis via direct interspecies electron transfer - Jun Xu; Ling Xu; Yang Zong; Rujing Lin; Yingying He; Li Xie (Bioresource Technology, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Effects of high-concentration influent suspended solids on aerobic granulation in sequencing batch reactors treating real textile wastewater - Jianrui Lin; Hangtian He; Jinte Zou; Yongyuan Yang; Jun Li (Journal of Water Process Engineering, 2024)

Study on low methoxyl pectin (LMP) with varied molecular structures cross-linked with calcium inducing differences in the gel properties - Chun-lin Wu; Jun-ru Qi; Jin-song Liao; Zi-wei Liu; Chun-ai He (Food Hydrocolloids, 2024)

Antioxidant response to ZnO nanoparticles in juvenile Takifugu obscurus: protective effects of salinity - Yuqing Lin; Jun Wang; Shufeng He; Hanlu Yan; Qiuwen Chen (Ecotoxicology, 2024)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Modeling of errors resulting from vehicle motions for CHZII mobile gravimeter and its performance verification during marine surveys - Hai-bo Tu; Jian-gang He; Ming Hu; Xing-hui Liang; Lei-jun Liu; Qin-qin Dong; Sun-jun Liu; Hui Zhang; Yong-tao Fu; Jun-jian Lang; Heng Sun; Lin-tao Liu (Applied Geophysics, 2023)

Enhanced impact of prolonged MHWs on satellite-observed chlorophyll in the South China Sea - Wenbo He; Xiyuan Zeng; Lin Deng; Qi Lin Chun Pi; Jun Zhao (Progress in Oceanography, 2023)

Propeller hydrodynamic excitation influenced by shafting whirling vibration considering different nonuniform inflow conditions: A numerical study - Chang-Lin Meng; Lie-Yi Dong; Dong-Hua Wang; Jia-Xuan He; Zhi-Jun Shuai; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Ocean Engineering, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Excellent hydration properties and oil holding capacity of citrus fiber: Effects of component variation and microstructure - Chun-ai He; Jun-ru Qi; Jin-song Liao; Ya-ting Song; Chun-lin Wu (Food Hydrocolloids, 2023)

In-situ utilization of EPS improves the directional oxidation ability of Fe(III)/H2O2 and enhances sludge dewaterability - Wei Lin; Chuangxin Gong; Renglu Chen; Xu He; Jun Nan; Guibai Li; Huu Hao Ngo; An Ding (Chemical Engineering Journal, 2023)

Characterization of Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov. and illumination of the distinct adaptative strategies of the genus Maribacter - Jia-Wei Gao; Jun-Jie Ying; Han Dong; Wen-Jia Liu; Dong-Yan He; Lin Xu; Cong Sun (Frontiers in Marine Science, 2023)
Polysaccharides are complex carbohydrates and are abundant in the marine environment. Microbes degrade and utilize them using Carbohydrate-active enzymes (CAZymes), which mediate polysaccharides into the marine carbon cycle. With the continued supply of polysaccharides from the marine environment, tidal flats are also abundant in polysaccharides, resulting in an abundance of marine polysaccharide degrading strains. In this study, three novel strains, designated as D37 T , M208 T , and SA7 T , were isolated from the intertidal sediment samples located in Zhoushan, Zhejiang and Huludao, Liaoning, PR China. The phylogenetic trees using the 16S rRNA gene and genome sequences showed that the three novel strains belonged to the genus Maribacter . The highest 16S rRNA gene sequence similarities between the three novel strains and other strains of the genus Maribacter were 98.7%, 99.2%, and 98.8%, respectively, while the ANI, AAI, and dDDH values between the three strains and the other strains of the genus Maribacter were 70-86%, 67-91%, and 17-30%, respectively, supporting their affiliation as novel species. Combined with other phenotypic and genotypic characterization in this study, three novel species are proposed as Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov., respectively, for the three strains. Furthermore, we compared all available genomes of Maribacter representatives and found that Maribacter strains could be divided into two groups (A and B). The two groups are different in genome size and G + C content and gene densities of CAZyme, peptidase, and sulfatase. Group A possesses more CAZymes which are related to degrading laminarin, fucoidan, mannan, xylose, and xylan. This result suggests that the two groups may have different niche adaptation strategies. Our study contributes to a better understanding of the role of marine flavobacteria in biogeochemical cycles and niche specialization.

Multi-technological integration in a smelting site: Visualizing pollution characteristics and migration pattern - Lu Tang; Wenwan Chen; Xinghua Luo; Gubin Zhang; Xiang Feng; Lin Guo; Wenyan Gao; Jin He; Guizhang Zhao; Jun Jiang; Shengguo Xue (Journal of Hazardous Materials, 2023)

Antimony immobilization mechanism on schwertmannite: Insights from the microstructure of schwertmannite - Jun Shan; Mengchang He; Peng Liu; Wenting Wang; Chunye Lin; Wei Ouyang; Xitao Liu; Jianwei Zhou; Haijiao Xie (Geochimica et Cosmochimica Acta, 2023)

Improving the quality and processing efficiency of beef jerky via drying in confined conditions of pre-stretching - Jun He; Wenzhe Jia; Zihan Lin; Yin Zhang; Yiguo Zhao; Yapeng Fang (Food Research International, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Assessment on the stereoselective behavior of cyflumetofen to earthworms (Eisenia foetida): Degradation, bioaccumulation, toxicity mechanism, and metabolites - Linlin Shi; Chao Shen; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phytochemistry and biological activities of corynanthe alkaloids - Jun Li; Jia-Xing Li; Hua Jiang; Min Li; Lin Chen; Yue-Yue Wang; Lu Wang; Ning Zhang; He-Zhe Guo; Kai-Long Ma (Phytochemistry, 2023)

Analysis of energy, exergy and CO2 emissions in a fiberglass furnace with oxy-fuel combustion - Yuan Yao; Jun-yao He; Qi Chen; Teng Li; Bo Li; Xiao-lin Wei (Fuel, 2023)

Baicalin promotes antiviral IFNs production and alleviates type I IFN-induced neutrophil inflammation - Li Li; Jia-Min Dong; He-He Ye; Man-Jing Jiang; Huan-Hua Yang; Lin-Pan Liang; Li-Jun Ning; Ying Wu (Journal of Natural Medicines, 2023)

Anti-inflammatory ent-cleistanthane-type diterpenoids from Phyllanthus rheophyticus - Hong-Ying Yang; Pei-Zhi Huang; Qian Ma; Yue Sun; Wei-Jiao Feng; Yi-Lin He; Jian-Jun Chen; Kun Gao (Phytochemistry, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Scour effects on the vertical dynamic response of single piles in transversely isotropic soils - Chun Lin Liu; Zhi Yong Ai; Meng Xiong Tang; He Song Hu; Lu Jun Wang (Ocean Engineering, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

Kinetics and mechanism study of dyes degradation in electric field-promoting catalytic wet air oxidation process - Lin-Feng Zhai; Yi Hu; Shu-Ya Xu; He-You Guo; Min Sun; Jun Yu; Yan Wang (Journal of Environmental Management, 2023)

Locating geothermal resources using seismic exploration in Xian county, China - Xiting Long; Guilin Wang; Wenjing Lin; Jun Wang; Zhiqiang He; Juchang Ma; Xiaofei Yin (Geothermics, 2023)

Integrated fixed-film activated sludge systems in continuous-flow and batch mode acclimated from low to high aniline concentrations: Performance, mechanism and metabolic pathways - Nan-ping Wu; Qian Zhang; Bin Tan; Meng Li; Bing Lin; Jing He; Jun-hao Su; Hao-nan Shen (Bioresource Technology, 2023)

Fine-tuning immunity against cancer: the emergence of engineered commensal microbiota - Shi-Jun He; Fan Yang; Jian-Ping Zuo; Ze-Min Lin (Science Bulletin, 2023)

Stelleratenoids A−F, macrocyclic daphnane orthoesters with anti-HIV activity from the roots of Stellera chamaejasme L. - Kang Ding; Zi-Yao Wu; Nuan Zhang; Jun He; Fan Zhang; Jing-Jing Wu; Hong-Jin Bai; Wei-Ku Zhang; Lin Li; Jie-Kun Xu (Phytochemistry, 2023)

Systematic assessment of cyflumetofen toxicity in soil-earthworm (Eisenia fetida) microcosms - Linlin Shi; Ping Zhang; Jun Xu; Xiaohu Wu; Xinglu Pan; Lin He; Fengshou Dong; Yongquan Zheng (Journal of Hazardous Materials, 2023)

Morphological and molecular identification of a new species, Trullella yunnanensis (Steccherinaceae, Polyporales) from southern China - Xiao He; Jun-Hong Dong; Chang-Lin Zhao (Kew Bulletin, 2023)

Effects of phosphorus fertilizer application rate on transformation processes of phosphorus fractions in the purple alluvial soil of a riparian zone - Li-ping He; Kai-tao Jia; Dan Liu; Ke-hong Wang; Lin-Yan Duan; Jun-jie Lin (Journal of Mountain Science, 2023)

Fabrication of crack-free oxidic thorium–cerium microspheres by an external gelation process - He Huang; Peng Wang; Chao Yan; Xiaohe Yu; Changqing Cao; Jun Lin; Zhiyong Zhu (Annals of Nuclear Energy, 2023)

Response of soil microbial activities and ammonia oxidation potential to environmental factors in a typical antimony mining area - Aihua Wang; Shujun Liu; Jun Xie; Wei Ouyang; Mengchang He; Chunye Lin; Xitao Liu (Journal of Environmental Sciences, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Triassic granitoids in the East Kunlun Orogenic Belt, Northwestern China: magmatic source and implications for geodynamic evolution - Zhi-He Xu; Wei Xin; Xiao-Dong Zhou; Qing-Lin Xu; Fu-Wen Li; Zhao-Jun Song (International Geology Review, 2023)

Unveiling the effect of structural water on Zn-ion storage of polyoxovanadate for high-rate and long-life aqueous zinc ion battery - Huan He; Fu-Chun Pan; Xue-Wei Liang; Qiang Hu; Shude Liu; Jisong Hu; Seong Chan Jun; Dunmin Lin; Yusuke Yamauchi; Yu Huo (Chemical Engineering Journal, 2023)

Internal driving mechanism of microbial community and metabolic pathway for psychrophilic anaerobic digestion by microbial electrolysis cell - Xiaomei Zheng; Jun Xu; Rujing Lin; Yingying He; Yaqing Yu; Yue Zhang; Li Xie (Bioresource Technology, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Effect of feeding level on growth, digestive and metabolic enzymes and antioxidant capacity in juvenile Yangtze sturgeon (Acipenser dabryanus) - Bin He; Bo Zhou; Hang Xie; Zeng-Tan Hu; Bin Wang; Jun-Lin Zhang; Qing-Zhi Li; Feng-Qi Zhao; Xing Liu; Qian-Dong Li; Tao Yan (Aquaculture, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Cobalt exposure and dyslipidemia in elderly population: the mediating role of systemic inflammation and lipid peroxidation - Jia-Hui Huang; Li Tao; Yi Wu; Wei He; Jun-Xian Wang; Xi Chen; Lin Fu (Environmental Science and Pollution Research, 2023)

Activation of persulfate by vanadium oxide modified carbon nanotube for 17β-estradiol degradation in soil: Mechanism, application and ecotoxicity assessment - Zhou Zhou; Xitao Liu; Jun Ma; Jun Huang; Chunye Lin; Mengchang He; Wei Ouyang (Science of The Total Environment, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

The construction of magnetic hydroxyapatite-functionalized pig manure-derived biochar for the efficient uranium separation - Jun Liao; Xiaoshan He; Yong Zhang; Lin Zhang; Zhibing He (Chemical Engineering Journal, 2023)

Spatial distribution and driving factors of sediment net nitrogen mineralization in riparian zone of the Three Gorges Reservoir - Kai-tao Jia; Li-ping He; Ke-hong Wang; Zhi-guo Yu; Li-jiao Liang; Zhuo-lin Yu; Jun-jie Lin (Journal of Mountain Science, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

Rainfall interception measurements and modeling in a semiarid evergreen spruce (Picea crassifolia) forest - Junjun Yang; Zhibin He; Jianmin Feng; Pengfei Lin; Jun Du; Lingxia Guo; Yufeng Liu; Jialiang Yan (Agricultural and Forest Meteorology, 2023)

Trace Element Changes in the Plasma of Autism Spectrum Disorder Children and the Positive Correlation Between Chromium and Vanadium - Jun Zhang; Jing Lin; Xiying Zhao; Fang Yao; Chengyun Feng; Zhijun He; Xueshan Cao; Yan Gao; Naseer Ullah Khan; Margy Chen; Peng Luo; Liming Shen (Biological Trace Element Research, 2022)

Dynamic response and failure evolution of low-angled interbedding soft and hard stratum rock slope under earthquake - Jun Feng; Yingbin Zhang; Jianxian He; Hui Zhu; Lin Huang; Wentao Mao; Haiying Fu; Dejian Li (Bulletin of Engineering Geology and the Environment, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Novel Self-Assembled Micelles With Increased Tumor Penetration and Anti-Tumor Efficiency Against Breast Cancer - Yani Yang; Yuezhu Zhao; Jie Liu; Chen Ge; Weiwei Zhang; Yue Zhang; Junji Wang; Guohao Sun; Xiujun Lin; Xiaohong Lu; Xiang Tang; Jun He; et al. (Pharmaceutical Research, 2022)

Extracellular histones induce inflammation and senescence of vascular smooth muscle cells by activating the AMPK/FOXO4 signaling pathway - Hang Yang; Yong-Yan Luo; Lue-Tao Zhang; Kai-Ran He; Xiao-Jun Lin (Inflammation Research, 2022)

Geomechanics model test and numerical simulation of 2G-NPR bolt support effect in an active fault tunnel - Shu-lin Ren; Man-chao He; Wei-jun Lin; Teng-wu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2022)

Age, Growth and Population Structure Analyses of the Purpleback Flying Squid Sthenoteuthis oualaniensis in the Northwest Indian Ocean by Beak Microstructure - Hua-Jie Lu; Yu-Zhe Ou; Jing-Ru He; Mao-Lin Zhao; Zi-Yue Chen; Xin-Jun Chen (Journal of Marine Science and Engineering, 2022)
To explore the feasibility of using beak microstructure information to estimate the age of Sthenoteuthis oualaniensis, the microstructures of the upper beaks of individual squid were applied in this work to analyze the ages and growth patterns of squid caught from February–May 2019 and from October–December 2020 in the northwest Indian Ocean. The results indicated that the squid samples in the two years were no older than 9 months, and the samples in 2019 were autumn population and 2020 were spring population. The linear growth model of the autumn population (2019) was the best model for describing the relationship between age and ML, while the power model of the spring population (2020) was the best for describing the relationship between age and ML. The maximum instantaneous growth rate (IGR) and absolute daily growth rate (AGR) values of the spring population were 0.24%/d and 1.09 mm/d, respectively, occurring in squid between 200 and 220 days of age. The maximum IGR and AGR values of the autumn population were 0.69%/d and 1.73 mm/d, respectively, occurring in squid between 200 and 240 days of age. The period from 141–260 days (5–8 months) was considered to correspond to the subadult stage in the whole life history of S. oualaniensis in the Northwest Indian Ocean. The beak microstructure information can be effectively applied to estimate the age of S. oualaniensis individuals.

Response of sap flow in Qinghai spruce (Picea crassifolia) to environmental variables in the Qilian Mountains of China - Jing Fang; Quanyan Tian; Zhibin He; Jun Du; Longfei Chen; Pengfei Lin; Xi Zhu (Trees, 2022)

Engineering an oilseed crop for hyper-accumulation of carotenoids in the seeds without using a traditional marker gene - Ming-Xia He; Jie-Lin Wang; Yuan-Yuan Lin; Jun-Chao Huang; Ai-Zhong Liu; Feng Chen (Plant Cell Reports, 2022)

Three-dimensional modeling and porosity calculation of coal rock pore structure - Qiong Li; Zheng Chen; Lin Yue; Yu Zhang; Jian-Jun He; Yong Li (Applied Geophysics, 2022)

Natural component plumbagin as a potential antibacterial agent against Streptococcus agalactiae infection - Ai‐Guo Huang; Lin‐Jun Su; Wei‐Hao He; Fa‐Li Zhang; Chao‐Shuai Wei; Ying‐Hui Wang (Journal of Fish Diseases, 2022)
Streptococcus agalactiae , also known as Group B Streptococcus (GBS), can infect humans, terrestrial animals and fish. The emergence of bacterial resistance of S. agalactiae to antibiotics leads to an urgent need of exploration of new antimicrobial agents. In the study, the antibacterial activity of natural component plumbagin (PLB) against S. agalactiae was investigated in vitro and in vivo. The results showed that the minimal inhibitory concentration (MIC) of PLB against S. agalactiae was 8 mg/L. The growth curve assay revealed that PLB could inhibit the growth of S. agalactiae . In addition, the time‐killing curve showed that S. agalactiae was killed almost completely by 2‐fold MIC of PLB within 12 h. Transmission electron microscopy results showed obvious severe morphological destruction and abnormal cells of S. agalactiae after treated with PLB. The pathogenicity of S. agalactiae to zebrafish was significantly decreased after preincubation with PLB for 2 h in vitro, further indicating the bactericidal activity of PLB. Interestingly, PLB could kill S. agalactiae without inducing resistance development. Furthermore, pretreatment and post‐treatment assays suggested that PLB also exhibited the antibacterial activity against S. agalactiae infection in vivo by effectively reducing the bacterial load and improving the survival rate of S. agalactiae ‐infected zebrafish. In summary, PLB had potent antibacterial activity against S. agalactiae in vitro and in vivo, and it could be an excellent antimicrobial candidate to prevent and control S. agalactiae infection.

Genetic diversity and population structure of Curcuma alismatifolia Gagnep. accessions revealed by SSR markers - Hui-Wen Yu; Ling-Jun Ke; Yi-Lan Xiao; Si-Jia Chen; Yuan-Yuan Li; Qi-Lin Tian; Yun-He Li; Jin-Shui Lin; Luan-Mei Lu (Genetic Resources and Crop Evolution, 2022)

Responses of soil pH to no‐till and the factors affecting it: A global meta‐analysis - Xin Zhao; Cong He; Wen‐Sheng Liu; Wen‐Xuan Liu; Qiu‐Yue Liu; Wei Bai; Li‐Jun Li; Rattan Lal; Hai‐Lin Zhang (Global Change Biology, 2022)
No‐till (NT) is a sustainable option because of its benefits in controlling erosion, saving labor, and mitigating climate change. However, a comprehensive assessment of soil pH response to NT is still lacking. Thus, a global meta‐analysis was conducted to determine the effects of NT on soil pH and to identify the influential factors and possible consequences based on the analysis of 114 publications. When comparing tillage practices, the results indicated an overall significant decrease by 1.33 ± 0.28% in soil pH under NT than that under conventional tillage ( p −1 (−1.83%), or crop residue retention (−1.52%). Changes in organic matter decomposition under undisturbed soil and with crop residue retention might lead to a higher concentration of H + and lower of basic cations (i.e., calcium, magnesium, and potassium), which decrease the soil pH, and consequently, impact nutrient dynamics (i.e., soil phosphorus) in the surface layer under NT. Furthermore, soil acidification may be aggravated by NT within site‐specific conditions and improper fertilizer and crop residue management and consequently leading to adverse effects on soil nutrient availability. Thus, there is a need to identify strategies to ameliorate soil acidification under NT to minimize the adverse consequences.

A dice similarity measure for TBM penetrability classification in hard rock condition with the intuitionistic fuzzy information of rock mass properties - Rui Yong; Jun Ye; Shi-Gui Du; He Zhang; Leiyu Gu; Hang Lin (European Journal of Environmental and Civil Engineering, 2021)

Impact of climate change on alpine plant community in Qilian Mountains of China - Jun Du; Zhibin He; Longfei Chen; Pengfei Lin; Xi Zhu; Quanyan Tian (International Journal of Biometeorology, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Skvortzovia yunnanensis, a new species of corticioid fungus from southern China - Jun-Hong Dong; Xiao He; Chang-Lin Zhao (Kew Bulletin, 2021)

Protective effect of Bombyx mori gloverin on intestinal epithelial cells exposure to enterotoxigenic E. coli - Qian Lin; Qingqing Fu; Guoqi Su; Daiwen Chen; Bing Yu; Yuheng Luo; Ping Zheng; Xiangbing Mao; Zhiqing Huang; Jie Yu; Junqiu Luo; Hui Yan; et al. (Brazilian Journal of Microbiology, 2021)

Identification of a delayed leaf greening gene from a mutation of pummelo - Hui-Wen Yu; Zhi-Hao Lu; Xia Wang; Dan Liu; Jia-Xian He; Xiao-Lin Jiang; Ling-Jun Ke; Wen-Wu Guo; Xiu-Xin Deng; Qiang Xu (Science China Life Sciences, 2021)

TRPV4 Regulates Soman-Induced Status Epilepticus and Secondary Brain Injury via NMDA Receptor and NLRP3 Inflammasome - Shuai Wang; Huanhuan He; Jianhai Long; Xin Sui; Jun Yang; Guodong Lin; Qian Wang; Yongan Wang; Yuan Luo (Neuroscience Bulletin, 2021)

Ghrelin Affects Gastric Cancer Progression by Activating AMPK Signaling Pathway - Xiao-Lin Hu; Yong-Jun Zhu; Chang-Hua Hu; Li You; Juan Wu; Xiao-Yan He; Wen-Jie Huang; Zong-Hui Wu (Biochemical Genetics, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Sun glint correction with an inherent optical properties data processing system - Jun Chen; Xianqiang He; Zhongli Liu; Nan Lin; Qianguo Xing; Delu Pan (International Journal of Remote Sensing, 2021)

Identification of 5S and 45S rDNA sites in Chrysanthemum species by using oligonucleotide fluorescence in situ hybridization (Oligo-FISH) - Jun He; Sisi Lin; Zhongyu Yu; Aiping Song; Zhiyong Guan; Weimin Fang; Sumei Chen; Fei Zhang; Jiafu Jiang; Fadi Chen; Haibin Wang (Molecular Biology Reports, 2021)

GPI7‐mediated glycosylphosphatidylinositol anchoring regulates appressorial penetration and immune evasion during infection of Magnaporthe oryzae - Caiyun Liu; Junjie Xing; Xuan Cai; Ahmed Hendy; Wenhui He; Jun Yang; Junbing Huang; You‐Liang Peng; Lauren Ryder; Xiao‐Lin Chen (Environmental Microbiology, 2020)
Summary Glycosylphosphatidylinositol (GPI) anchoring plays key roles in many biological processes by targeting proteins to the cell wall; however, its roles are largely unknown in plant pathogenic fungi. Here, we reveal the roles of the GPI anchoring in Magnaporthe oryzae during plant infection. The GPI‐anchored proteins were found to highly accumulate in appressoria and invasive hyphae. Disruption of GPI7 , a GPI anchor‐pathway gene, led to a significant reduction in virulence. The Δ gpi7 mutant showed significant defects in penetration and invasive growth. This mutant also displayed defects of the cell wall architecture, suggesting GPI7 is required for cell wall biogenesis. Removal of GPI‐anchored proteins in the wild‐type strain by hydrofluoric acid (HF) pyridine treatment exposed both the chitin and β‐1,3‐glucans to the host immune system. Exposure of the chitin and β‐1,3‐glucans was also observed in the Δ gpi7 mutant, indicating GPI‐anchored proteins are required for immune evasion. The GPI anchoring can regulate subcellular localization of the Gel proteins in the cell wall for appressorial penetration and abundance of which for invasive growth. Our results indicate the GPI anchoring facilitates the penetration of M. oryzae into host cells by affecting the cell wall integrity and the evasion of host immune recognition.

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Daily minimum temperature and precipitation control on spring phenology in arid‐mountain ecosystems in China - Jun Du; Kai Li; Zhibin He; Longfei Chen; Pengfei Lin; Xi Zhu (International Journal of Climatology, 2020)
Climate anomaly has caused substantial shifts in phenology of mountain ecosystems, but the underlying mechanism of phenological responses to climate change is still not well understood. In essence, the abundance of vegetation communities increases the complexity of phenology‐climate relationships, leading to a certain limitation in predictions of future dynamics among different vegetation types using a unified model. In this study, we focused on the climatic constraints on spring phenology in arid mountains (AMs) of China, and emphasis was laid on accurate representation of mechanisms that control phenology across different vegetation types. We Firstly explored spatio‐temporal variations in satellite‐derived estimates of starting date of vegetation growing season (SOS) over the period 2000–2015 using moderate‐resolution imaging spectro‐radiometer (MODIS) normalized difference vegetation index (NDVI). Phenological models in response to climate variability were then established by using mixed‐effect models based on satellite observations and an extensive dataset of climatic measurements. Our results showed that the climatic regulation on SOS varied greatly over vegetation types. More climatic factors that regulate phenological development were found in grassland than forest and shrubland. At ecosystem level, two critical climate factors, daily minimum temperature ( T min ) and precipitation, explained 74–95% of total variability in predicted SOS. The observed sensitivity to T min is expected to be closely linked with the risk of frost damage, while preseason precipitation determines water availability in spring. The varying ecosystem sensitivity revealed the different resilience and adaptability to changing climate among vegetation types, which have been linked to their eco‐physiological characteristics (e.g., water use efficiency) and environmental conditions (e.g., elevation). Overall, our results indicate a strong dependence of spring phenology on T min and precipitation, and create an opportunity for a more realistic representation of vegetation phenology and growth of AM plants in China in land surface models.

Combined GWAS and QTL analysis for dissecting the genetic architecture of kernel test weight in maize - Xiaoxiang Zhang; Zhongrong Guan; Lei Wang; Jun Fu; Yinchao Zhang; Zhaoling Li; Langlang Ma; Peng Liu; Yanling Zhang; Min Liu; Peng Li; Chaoying Zou; et al. (Molecular Genetics and Genomics, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

Macrobenthic communities on the continental shelf of the Prydz Bay, East Antarctica - Kun Liu; Heshan Lin; Xuebao He; Yaqin Huang; Zhong Li; Junhui Lin; Jianfeng Mou; Shuyi Zhang; Jianjun Wang; Jun Sun (Acta Oceanologica Sinica, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Seasonal Dynamics of Gastrointestinal Nematode Infections of Goats and Emergence of Ivermectin Resistance in Haemonchus contortus in Hubei Province, China - Wei Yuan; Ke Lu; Hao Li; Jinming Liu; Chuanchuan He; Jintao Feng; Xin Zhang; Yudan Mao; Yang Hong; Yu Zhou; Jun Lu; Yamei Jin; et al. (Acta Parasitologica, 2019)

MOF Capacitates Cyclodextrin to Mega-Load Mode for High-Efficient Delivery of Valsartan - Wei Zhang; Tao Guo; Caifen Wang; Yuanzhi He; Xi Zhang; Guangyu Li; Yizhi Chen; Jun Li; Yangjing Lin; Xu Xu; Li Wu; Suxia Zhang; et al. (Pharmaceutical Research, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Characterization of the Cd(II) and nitrate removal by bacterium Acinetobacter sp. SZ28 under different electron donor conditions - Jun Feng Su; Chun Yu Gao; Ting Lin Huang; Xue Chen Bai; Dong Hui Liang; Lei He (Environmental Science and Pollution Research, 2019)

Correction to: Efficient removal of dyes from dyeing wastewater by powder activated charcoal/titanate nanotube nanocomposites: adsorption and photoregeneration - Yingchao Lin; Jun Ma; Wen Liu; Zeyu Li; Kai He (Environmental Science and Pollution Research, 2019)

Efficient removal of dyes from dyeing wastewater by powder activated charcoal/titanate nanotube nanocomposites: adsorption and photoregeneration - Yingchao Lin; Jun Ma; Wen Liu; Zeyu Li; Kai He (Environmental Science and Pollution Research, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Correction to: Ready player one? Autophagy shapes resistance to photodynamic therapy in cancers - Xian Duan; Bo Chen; Yanan Cui; Lin Zhou; Chenkai Wu; Zhulin Yang; Yu Wen; Xiongying Miao; Qinglong Li; Li Xiong; Jun He (Apoptosis, 2019)

Permian integrative stratigraphy and timescale of China - Shuzhong Shen; Hua Zhang; Yichun Zhang; Dongxun Yuan; Bo Chen; Weihong He; Lin Mu; Wei Lin; Wenqian Wang; Jun Chen; Qiong Wu; Changqun Cao; et al. (Science China Earth Sciences, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Ready player one? Autophagy shapes resistance to photodynamic therapy in cancers - Xian Duan; Bo Chen; Yanan Cui; Lin Zhou; Chenkai Wu; Zhulin Yang; Yu Wen; Xiongying Miao; Qinglong Li; Li Xiong; Jun He (Apoptosis, 2018)

A new Tanay virus isolated from mosquitoes in Guangxi, China - Jinglin Wang; Jianming Wu; Nan Li; Yingying Cao; Yuwen He; Jun Lin; Huachun Li (Archives of Virology, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Spatial patterns in natural Picea crassifolia forests of northwestern China, as basis for close-to-nature forestry - Zhi-bin He; Shu Fang; Long-fei Chen; Jun Du; Xi Zhu; Peng-fei Lin (Journal of Mountain Science, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Mixed Cadzow filtering method in fractional Fourier domain - Zhong-Lin Cao; Jun-Xing Cao; Fu-Rong Wu; Guang-Ming He; Qiang Zhou; Yu-Lin Wu (Applied Geophysics, 2018)

Impacts of climate change on reference evapotranspiration in the Qilian Mountains of China: Historical trends and projected changes - Pengfei Lin; Zhibin He; Jun Du; Longfei Chen; Xi Zhu; Jing Li (International Journal of Climatology, 2018)
Global climate change is likely to affect reference evapotranspiration (ET 0 ) and the use of water resources for vegetation management. Our goals were to identify spatio‐temporal characteristics of ET 0 and factors controlling the change in ET 0 and to project spatio‐temporal changes in the Qilian Mountains of China under the future climate conditions. Changes in ET 0 were estimated by the Penman–Monteith method for 22 meteorological stations from 1960 to 2015. We quantified the attributions of climatic factors with the differentiation equation method. Then, we assessed the spatio‐temporal changes in projected ET 0 with CanESM2 model outputs and statistical downscaling model for three representative concentration pathways (RCP) scenarios for years 2016–2100. We found that annual ET 0 averaged across the region was 1001.5 mm, with an insignificant decrease of −0.43 mm/year during 1960–2015. The lowest values were present in the alpine region in the central area, while the highest ET 0 was detected in the western region. An annual and seasonal “evaporation paradox” existed in the Qilian Mountains during the past few decades. Mean daily air temperature measured ( T mean ) and wind speed ( U 2 ) were the dominant factors in ET 0 change. However, the decreasing trend in ET 0 may be due to a diminished effect of T mean triggered by short‐wave radiation ( R s ), actual vapour pressure ( e a ), and wind speed ( U 2 ), but especially by the substantial reduction in U 2 at most stations. Compared with the baseline, ET 0 is likely to increase by 6.31–7.20, 6.11–10.41, and 6.58–17.66%, respectively, under RCP scenarios of 2.6 (very low forcing scenario), 4.5 (medium stabilization scenario), and 8.5 (very high emission scenario), but RCP2.6 ET 0 rates level off and even decline after 2050 while RCP4.5 rates climb only marginally after 2050. Thus, ET 0 projected with the CanESM2 model displayed an upwards trend in the Qilian Mountains, especially the central alpine region.

Necroptosis may be a novel mechanism for cardiomyocyte death in acute myocarditis - Fei Zhou; Xuejun Jiang; Lin Teng; Jun Yang; Jiawang Ding; Chao He (Molecular and Cellular Biochemistry, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Comparing strategies for selection of low-density SNPs for imputation-mediated genomic prediction in U. S. Holsteins - Jun He; Jiaqi Xu; Xiao-Lin Wu; Stewart Bauck; Jungjae Lee; Gota Morota; Stephen D. Kachman; Matthew L. Spangler (Genetica, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Variations in cadmium and nitrate co-accumulation among water spinach genotypes and implications for screening safe genotypes for human consumption - Lin Tang; Wei-jun Luo; Zhen-li He; Hanumanth Kumar Gurajala; Yasir Hamid; Kiran Yasmin Khan; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2018)

Cyclooxygenase-2 (COX-2) polymorphism rs689466 may contribute to the increased susceptibility to post-traumatic osteomyelitis in Chinese population - Lei Wang; Nan Jiang; Qing-rong Lin; Cheng-he Qin; Yan-jun Hu; Bin Yu (Infectious Diseases, 2017)

Association mapping analysis of fiber yield and quality traits in Upland cotton (Gossypium hirsutum L.) - Mulugeta Seyoum Ademe; Shoupu He; Zhaoe Pan; Junling Sun; Qinglian Wang; Hongde Qin; Jinhai Liu; Hui Liu; Jun Yang; Dongyong Xu; Jinlong Yang; Zhiying Ma; et al. (Molecular Genetics and Genomics, 2017)

Inhibitory effects of Dioscin on atherosclerosis and foam cell formation in hyperlipidemia rats - Ping Wang; Li-ya He; Guo-dong Shen; Rui-lin Li; Jun-li Yang (Inflammopharmacology, 2017)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

Phenolic compounds from the stems of Flickingeria fimbriata - Ya-Ping Wu; Wen-Jian Liu; Wen-Jun Zhong; Yue-Juan Chen; Dan-Na Chen; Feng He; Lin Jiang (Natural Product Research, 2017)

Iron supply prevents Cd uptake in Arabidopsis by inhibiting IRT1 expression and favoring competition between Fe and Cd uptake - Xiao Lin He; Shi Kan Fan; Jun Zhu; Mei Yan Guan; Xing Xing Liu; Yong Song Zhang; Chong Wei Jin (Plant and Soil, 2017)

Prevalence and spectrum of thalassaemia in Changsha, Hunan province, China: discussion of an innovative screening strategy - Jun He; Houlin Zeng; Lin Zhu; Hanmei Li; Liangcheng Shi; Lanping Hu (Journal of Genetics, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

A Review of the Functional and Anatomical Default Mode Network in Schizophrenia - Mao-Lin Hu; Xiao-Fen Zong; J. John Mann; Jun-Jie Zheng; Yan-Hui Liao; Zong-Chang Li; Ying He; Xiao-Gang Chen; Jin-Song Tang (Neuroscience Bulletin, 2017)

Prolonged exposure to low-dose microcystin induces nonalcoholic steatohepatitis in mice: a systems toxicology study - Jun He; Guangyu Li; Jun Chen; Juan Lin; Cheng Zeng; Jing Chen; Junliang Deng; Ping Xie (Archives of Toxicology, 2017)

Tetrasomic inheritance pattern of the pentaploid Solanum chacoense (+) S. tuberosum somatic hybrid (resistant to bacterial wilt) revealed by SSR detected alleles - Lin Chen; Xianpu Guo; Haibo Wang; Conghua Xie; Xingkui Cai; Li He; Jun Zhou; Jun Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Regulation and the Mechanism of Estrogen on Cav1.2 Gene in Rat-Cultured Cortical Astrocytes - Ling He; Xiao-Tong Hu; Yu-Jie Lai; Yan Long; Lu Liu; Bing-lin Zhu; Guo-Jun Chen (Journal of Molecular Neuroscience, 2016)

Aquatic bioaccumulation and trophic transfer of tetrabromobisphenol-A flame retardant introduced from a typical e-waste recycling site - Lin Tao; Jiang-Ping Wu; Hui Zhi; Ying Zhang; Zi-He Ren; Xiao-Jun Luo; Bi-Xian Mai (Environmental Science and Pollution Research, 2016)

A novel process for obtaining pinosylvin using combinatorial bioengineering in Escherichia coli - Jing-long Liang; Li-qiong Guo; Jun-fang Lin; Ze-qi He; Fa-ji Cai; Jun-fei Chen (World Journal of Microbiology and Biotechnology, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Soil organic carbon pool along different altitudinal level in the Sygera Mountains, Tibetan Plateau - He-ping Ma; Xiao-lin Yang; Qi-qiang Guo; Xin-jun Zhang; Chen-ni Zhou (Journal of Mountain Science, 2016)

Ecological status classification of the Taizi River Basin, China: a comparison of integrated risk assessment approaches - Juntao Fan; Elena Semenzin; Wei Meng; Elisa Giubilato; Yuan Zhang; Andrea Critto; Alex Zabeo; Yun Zhou; Sen Ding; Jun Wan; Mengchang He; Chunye Lin (Environmental Science and Pollution Research, 2015)

Identification of genes involved in biosynthesis of mannan polysaccharides in Dendrobium officinale by RNA-seq analysis - Chunmei He; Jianxia Zhang; Xuncheng Liu; Songjun Zeng; Kunlin Wu; Zhenming Yu; Xiaojuan Wang; Jaime A. Teixeira da Silva; Zijian Lin; Jun Duan (Plant Molecular Biology, 2015)

High-efficiency propagation of Chinese water chestnut [Eleocharis dulcis (Burm.f.) Trin. ex Hensch] using a temporary immersion bioreactor system - Meiping Gao; Wen Jiang; Shaolong Wei; Zhicheng Lin; Binghua Cai; Liu Yang; Cong Luo; Xinhua He; Jun Tan; Lijuan Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

AVO forwarding modeling in two-phase media: multiconstrained matrix mineral modulus inversion - Kai Lin; Zhen-Hua He; Xiao-Jun Xiong; Xi-Lei He; Jun-Xing Cao; Ya-Juan Xue (Applied Geophysics, 2014)

Preliminary analysis of spatiotemporal pattern of global land surface water - Xin Cao; Jun Chen; LiJun Chen; AnPing Liao; FangDi Sun; Yang Li; Lei Li; ZhongHui Lin; ZhiGuo Pang; Jin Chen; ChaoYing He; Shu Peng (Science China Earth Sciences, 2014)

An adaptive noise attenuation method for edge and amplitude preservation - Han-Peng Cai; Zhen-Hua He; Ya-Lin Li; Guang-Ming He; Wen Zou; Dong-Jun Zhang; Pu Liu (Applied Geophysics, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Sustained endoplasmic reticulum stress inhibits hepatocyte proliferation via downregulation of c-Met expression - Yihuai He; Jun Long; Weiwei Zhong; Yu Fu; Ying Li; Shide Lin (Molecular and Cellular Biochemistry, 2014)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

PXR polymorphisms and their impact on pharmacokinetics/pharmacodynamics of repaglinide in healthy Chinese volunteers - Qing-qing Du; Zhi-jun Wang; Lin He; Xue-hua Jiang; Ling Wang (European Journal of Clinical Pharmacology, 2013)

Gold complexes inhibit the aggregation of prion neuropeptides - Xuesong Wang; Lei He; Cong Zhao; Weihong Du; Jun Lin (JBIC Journal of Biological Inorganic Chemistry, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

The optimal fractional Gabor transform based on the adaptive window function and its application - Ying-Pin Chen; Zhen-Ming Peng; Zhen-Hua He; Lin Tian; Dong-Jun Zhang (Applied Geophysics, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Nuclear and cytoplasmic genome components of Solanum tuberosum + S. chacoense somatic hybrids and three SSR alleles related to bacterial wilt resistance - Lin Chen; Xianpu Guo; Conghua Xie; Li He; Xingkui Cai; Lingli Tian; Botao Song; Jun Liu (Theoretical and Applied Genetics, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

The Flexible Global Ocean-Atmosphere-Land system model, Spectral Version 2: FGOALS-s2 - Qing Bao; Pengfei Lin; Tianjun Zhou; Yimin Liu; Yongqiang Yu; Guoxiong Wu; Bian He; Jie He; Lijuan Li; Jiandong Li; Yangchun Li; Hailong Liu; et al. (Advances in Atmospheric Sciences, 2013)

Influence of Rare Earth Elements on Metabolism and Related Enzyme Activity and Isozyme Expression in Tetrastigma hemsleyanum Cell Suspension Cultures - Peng Xin; Zhou Shuang-Lin; He Jun-Yao; Ding Li (Biological Trace Element Research, 2013)

Expression analysis, single nucleotide polymorphisms and combined genotypes in candidate genes and their associations with growth and carcass traits in Qinchuan cattle - Li-jun Wang; Xiao-lin Liu; Hong-liang Wang; Hua He; Zhi-xiong Li; Ling Chen (Molecular Biology Reports, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Novel differential transcript expression identified by LongSAGE in the mouse endometrium during the implantation window - Yu-Bin Ding; Jun-Lin He; Xue-Mei Chen; Xue-Qing Liu; Ying-Xiong Wang (Molecular Biology Reports, 2013)

A new isoform of thioredoxin h group in potato, SbTRXh1, regulates cold-induced sweetening of potato tubers by adjusting sucrose content - Tianjiu He; Botao Song; Jun Liu; Xia Chen; Yongbin Ou; Yuan Lin; Huiling Zhang; Conghua Xie (Plant Cell Reports, 2012)

Effect of active immunization against a recombinant mouse granulocyte-macrophage colony-stimulating factor/somatostatin fusion protein on the growth of mice - Bingbing Wu; Ruili Qi; Bin Li; Taoyan Yuan; Heshan Liu; Jun He; Zhiwei Lin; Weifen Li; Yan Fu; Dong Niu (Molecular Biology Reports, 2012)

Modulation of gene expression in cold-induced sweetening resistant potato species Solanum berthaultii exposed to low temperature - Xia Chen; Botao Song; Jun Liu; Jianwen Yang; Tianjiu He; Yuan Lin; Huiling Zhang; Conghua Xie (Molecular Genetics and Genomics, 2012)

FTH1 binds to Daxx and inhibits Daxx-mediated cell apoptosis - Fang Liu; Zhi-Yin Du; Jun-Lin He; Xue-Qing Liu; Qiu-Bo Yu; Ying-Xiong Wang (Molecular Biology Reports, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Inhibition of Lymphoma Cell Proliferation by Peroxisomal Proliferator-Activated Receptor-γ Ligands via Wnt Signaling Pathway - Jia-Jun Liu; Xue-Jun Dai; Yan Xu; Pei-Qing Liu; Yong Zhang; Xiao-Dan Liu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang (Cell Biochemistry and Biophysics, 2012)

High-precision frequency attenuation analysis and its application - Xiao-Jun Xiong; Xi-Lei He; Yong Pu; Zhen-Hua He; Kai Lin (Applied Geophysics, 2011)

Olig1 and ID4 interactions in living cells visualized by bimolecular fluorescence complementation technique - Shu-Jun Guo; Jian-Guo Hu; Bao-Ming Zhao; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü (Molecular Biology Reports, 2011)

PPARγ Agonist Suppresses TLR4 Expression and TNF-α Production in LPS Stimulated Monocyte Leukemia Cells - Chun-Zhi Wang; Yong Zhang; Xu-Dong Li; Yuan Hu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang; Pei-Qing Liu; Jia-Jun Liu (Cell Biochemistry and Biophysics, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Self-adapting extraction of matrix mineral bulk modulus and verification of fluid substitution - Kai Lin; Xiao-Jun Xiong; Xiao Yang; Zhen-Hua He; Jun-Xing Cao; Xi-Hua Zhang; Ping Wang (Applied Geophysics, 2011)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Prognostic significance of survivin expression in renal cell cancer and its correlation with radioresistance - Yu Lei; Zhang Geng; Wu Guo-Jun; Wang He; Yuan Jian-Lin (Molecular and Cellular Biochemistry, 2010)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways - Hong-Tao Liu; Jun-Lin He; Wen-Ming Li; Zhu Yang; Ying-Xiong Wang; Juan Yin; Yu-Guang Du; Chao Yu (Inflammation Research, 2010)

Protein sumoylation sites prediction based on two-stage feature selection - Lin Lu; Xiao-He Shi; Su-Jun Li; Zhi-Qun Xie; Yong-Li Feng; Wen-Cong Lu; Yi-Xue Li; Haipeng Li; Yu-Dong Cai (Molecular Diversity, 2010)

Characterization of the complete genome sequence of pike fry rhabdovirus - Hong-Lian Chen; Hong Liu; Zong-Xiao Liu; Jun-Qiang He; Long-Ying Gao; Xiu-Jie Shi; Yu-Lin Jiang (Archives of Virology, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

Establishment of cell lines using a doxycycline-inducible gene expression system to regulate expression of hepatitis B virus X protein - Hong Tang; Li Liu; Feng-Jun Liu; En-Qiang Chen; Seishi Murakami; Yong Lin; Fang He; Tao-You Zhou; Fei-Jun Huang (Archives of Virology, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Chymase induces profibrotic response via transforming growth factor-β1/Smad activation in rat cardiac fibroblasts - Xiao-Yan Zhao; Lian-You Zhao; Qiang-Sun Zheng; Jin-Lin Su; Hao Guan; Fu-Jun Shang; Xiao-Lin Niu; Yan-Ping He; Xiao-Long Lu (Molecular and Cellular Biochemistry, 2008)

Biosynthesis of γ-aminobutyric acid (GABA) using immobilized whole cells of Lactobacillus brevis - Jun Huang; Le-he Mei; Hong Wu; Dong-qiang Lin (World Journal of Microbiology and Biotechnology, 2007)

Using SSR markers to determine the population genetic structure of wild apricot (Prunus armeniaca L.) in the Ily Valley of West China - He Tian-Ming; Chen Xue-Sen; Xu Zheng; Gao Jiang-Sheng; Lin Pei-Jun; Liu Wen; Liang Qing; Wu Yan (Genetic Resources and Crop Evolution, 2007)

Reduction in the in vitro expression of Brain–Pancreas Relative Protein by oxygen and glucose-deprivation - Yan-Hua Lin; Ai-Hua Liu; Yan Pan; Christel Westenbroek; Gert J Ter Horst; He-Ming Yu; Xue-Jun Li (Molecular and Cellular Biochemistry, 2007)

Specific Phage-Displayed Peptides Binding to Tumor Vasculature - Yu Han; Liu Hong; Kaichun Wu; Shuhui Liang; Lin Xia; Shanshan Cao; Huihong Zhai; Jun Wang; Lijie He; Feihu Bai; Zhen Chen; Taidong Qiao; et al. (International Journal of Peptide Research and Therapeutics, 2006)

A rice transcription factor OsbHLH1 is involved in cold stress response - Yu-Jun Wang; Zhi-Gang Zhang; Xin-Jian He; Hua-Lin Zhou; Yu-Xiang Wen; Ji-Xun Dai; Jin-Song Zhang; Shou-Yi Chen (Theoretical and Applied Genetics, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)